Endocrine disruption: From a whole-lake experiment to a calibrated ecosystem model. (May 2019) - Clouzot, L.; Vanrolleghem, P.A.
Abstract: The unique Canadian whole-ecosystem study on the impact of 17α-ethinylestradiol (EE2) on a freshwater food web (Karen et al., 2014) provides evidence of the value of whole-ecosystem experiments for understanding indirect effects of endocrine disrupting compounds (EDCs) and other aquatic stressors. To further explain the indirect effects of EE2 observed in the experimental lake, an ecosystem model based on AQUATOX equations was successfully developed and calibrated. Discussions with the scientists who gathered the experimental data were necessary to ensure the consistency of the parameters used in the model and the realism of the biomass dynamics observed in such ecosystems. The prediction results helped further explain how the other fishes were impacted by the fathead minnow collapse. This study also suggests that a mix of reduced gamete production, increased gamete mortality and fish mortality is a potential mechanism for the collapse of the fathead minnow population. Highlights: An ecosystem model was developed and calibrated with a unique set of data from a whole-lake study on endocrine disruption. Ecological interactions, as well as lake stratification and physico-chemical dynamics are included in the model. The model presents potential hypotheses on the biological processes involved in endocrine disruption in fathead minnow. The model can successfully predict indirect effects of endocrine disruption on a freshwater food web.